صفحات من مسار الثورة التحريرية: أزمات الحكومة المؤقتة "1958-1959" - شبوب، محمد (جامعة وهران 1 أحمد بن بلة - مخبر البحث التاريخي مصادر وتراجم, 2017)
تتناول هذه الدراسة واحدة من المحطات التاريخية التي عرفها مسار الثورة التحريرية، حيث تعود وقائعها إلى فترة تأسيس الحكومة المؤقتة وتلك الأزمة التي حلت بها جراء الاختلاف الذي وقع بين قادة الثورة حول مبدأ الشرعية الثورية وأحقية الزعامة بسبب الانتماء السياسي، فشهدت خلافات عديدة وصراعات سياسية متكررة بين زعمائها، كادت أن تعصف بها لولا حنكة وحكمة بعض قادتها الذين عرفوا كيف يتحكمون في الوضع، ساعين إلى خلق توازن بين النضال السياسي والعسكري من أجل استمرار الثورة التحريرية واحتراما لبيان أول نوفمبر لغاية سامية هي تنظيم الثورة لتحقيق الاستقلال والحرية.
This study focuses on one of the events that the National Revolution knew. It was about the crisis that hit the Provisional Government (GPRA). This serious crisis was originally a leadership struggle, which took place between the leaders of the revolution on the principle of revolutionary legitimacy and eligibility of management because of their political affiliation. In fact, it has had many disputes and political conflicts between its leaders, having led the government to the impasse. But due to the wisdom of some of its leaders who were able to control the situation, trying to create a balance between the political and military struggle for the continuation of the revolution, it was the meeting of ten colonels to put end to this crisis, and so that it endows the revolution a new direction.
Keywords: الثورة التحريرية -- الحركات التحريرية -- النضال السياسي -- تاريخ الجزائر